Illustrating the incentivised steps criminals take to launder cash while avoiding government anti-laundering measures. Issue 2 (13th March 2020) - Gilmour, Nicholas
Abstract : Purpose: The purpose of this paper is to illustrate the incentivised steps criminals take to launder cash while avoiding government's anti-money laundering (AML) measures. Design/methodology/approach: To illustrate how and when technology is most prominent in the money laundering process, this paper analyses the criminal's methodological approach to "technology-enhanced money laundering" by examining several high-level examples. To strengthen the theoretical assessment and the overall validity of the findings, the author incorporates details from their own research and professional experience to maximise comprehension of the methodological process that organised criminals and money launderers alike look to undertake when placing illicitly derived cash in the money laundering cycle. Findings: The AML model of "placement, layering and integration" is synonymous with presenting the process of money laundering – in the most basic or generic forms. This paper identifies that the placement stage is a primary stage through which technology is exploited to assist in the entire laundering process. Practical implications: Using money laundering case studies, this paper identifies that existing AML/countering terrorism financing international perceptions/practices and typological studies are not adequate for presenting an accurate assessment of the process used to undertake money laundering. Originality/value: This paper provides an examination of the practicalities behind the prevention of money laundering from a compliance and investigative perspective. The paper is of interest to those involved in policy, compliance and investigations associated with money laundering.